2020
DOI: 10.3389/fncel.2020.00253
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Modulation of Signal Processing in a Subset of Retinal Bipolar Cells

Abstract: The retina and the olfactory bulb are the gateways to the visual and olfactory systems, respectively, similarly using neural networks to initiate sensory signal processing. Sensory receptors receive signals that are transmitted to neural networks before projecting to primary cortices. These networks filter sensory signals based on their unique features and adjust their sensitivities by gain control systems. Interestingly, dopamine modulates sensory signal transduction in both systems. In the retina, dopamine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 126 publications
0
7
0
3
Order By: Relevance
“…Recent work has suggested that D 1 Rs are expressed by most mouse cBCs, but not by all cBC subtypes (Farshi et al, 2016 ) and that D 1 R effects may be cBC subtype-specific (Hellmer et al, 2020 ). These results raise the interesting possibility that one important effect of D 1 Rs is to decorrelate the activity of different cBC subtypes, implying that ganglion cell subtypes and their post-synaptic targets through the visual system (Caldwell and Daw, 1978 ; Mangel et al, 1983 ; Troy and Shou, 2002 ; Wienbar and Schwartz, 2017 ) may be differentially affected as well.…”
Section: Dopamine-mediated Extrinsic Modulatory Processes In the Outer Retinamentioning
confidence: 99%
“…Recent work has suggested that D 1 Rs are expressed by most mouse cBCs, but not by all cBC subtypes (Farshi et al, 2016 ) and that D 1 R effects may be cBC subtype-specific (Hellmer et al, 2020 ). These results raise the interesting possibility that one important effect of D 1 Rs is to decorrelate the activity of different cBC subtypes, implying that ganglion cell subtypes and their post-synaptic targets through the visual system (Caldwell and Daw, 1978 ; Mangel et al, 1983 ; Troy and Shou, 2002 ; Wienbar and Schwartz, 2017 ) may be differentially affected as well.…”
Section: Dopamine-mediated Extrinsic Modulatory Processes In the Outer Retinamentioning
confidence: 99%
“…S7B). Retinal DA is reported to modulate the activity of bipolar cells and ERG b-wave amplitude via DA receptors, especially the D1 receptor [ 50 53 ]. To establish the involvement of DA signaling, DA D1 receptor antagonist—SCH23390—was intraperitoneally injected ~ 30 min before oxytocin application, and the effect of oxytocin-induced b-wave amplitude reduction disappeared (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DA D1 and D2 receptors are differently expressed in the retina, with D1 receptors expressed in a broad range of retinal neurons, whereas D2 receptors are mainly in photoreceptors and DA neurons [ 55 , 71 ]. Activating D1 receptors will increase the activity of GABA(A) receptors on dendrites of ON bipolar cells and also suppress voltage-gated calcium currents in some bipolar cells, which leads to a strong inhibition of the activity of bipolar cells and the reduction of ERG b-wave amplitude [ 52 , 53 ]. Previous studies also reported that the application of exogenous DA and its agonist decreased the amplitude of the b-wave in the mammalian retina [ 51 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…43,46,47 Dopamine is a retina neurotransmitter that regulates neural activity and integrates visual information. 48,49 The nuclei of dopaminergic cells are situated predominantly in the inner layers close to ganglion cells. Excessive glutamate synthesis, neuronal death, and cellular dysregulation may result from a dopamine deficit.…”
Section: Discussionmentioning
confidence: 99%